Interkoneksi Mahkamah Konstitusi Dengan Mahkamah Agung; Studi Implementasi Putusan Tentang Nasab Anak - Mesrain Mesraini (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2017)
This article examines the interconnection between constitutional courtand Supreme Court, with a special reference to the situation when Supreme Courtdecreed after the constitutional court decree. For the purpose of study, I use thedecree on the child’s descent case proposed by Machica Mohtar to examine theinterconnection of these two courts. By understanding how effective are theconstitutional court decrees and their connection with the position of SupremeCourt, I find that the interconnection between these religious court–high religiouscourts and constitutional court well-managed enough. Constitutional court decreehas been used as the basis for the court decrees. Nevertheless, Supreme Courttends not to place constitutional court decree for a permanent legal force (inkracht).As a result, the connection between constitutional court and Supreme Court hasnot been seen in its proper level. In another aspect, the implementation of law inIndonesia has shown a shifting from civil law system to those mixed between civillaw and common law systems. In this regard, this shifting indicates that not onlydoes a judge decree based on a procedural-justice, but he/she also takes asubstantive-justice into consideration. DOI: 10.15408/sjsbs.v4i1.7866